Learning history: are all students learns the same? - Burhanuddin, Nur Aimi Nasuha; G Sritharen, Shakthy Thashayini (Human Resources Management Academic Research Society, 2024)
History subject is one of the compulsories passing subject in the national examination for Malaysian secondary school students. The decision has brought a shift in the teaching and learning. The role of learning style provides a flexibility in learning that may indirectly shape a positive attitude that would create a better approach in teaching and learning of the subject. This qualitative study applied semi-structured interview with secondary school students exploring the preferred learning style of secondary school students in learning the History subject. A total of 7 students from the upper level of secondary school was interviewed with consent and in adherence to the ethical guidelines of conducting a study. The current findings demonstrated the effectiveness of learning style and learning attitude of secondary school students in learning the History subject. Future studies on learning style are recommended to focus on the different level of education from primary to pre-university as well differences in gender on applying learning style to learn the History subject. One more focus of study could be implied on the effectiveness of learning attitude formation with matched teaching style and learning style of learning the History subject in school.